Development of a Realistic Mathematics Education (RME)-Based Learning Module on Trigonometry for Grade X Vocational High School (SMK) Students - Rana Anjani (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
This study aims to develop a learning module based on the Realistic Mathematics Education (RME) approach for Grade X vocational high school (SMK) students, focusing on the topic of Trigonometry. The research employs a Research and Development (R&D) design, adopting the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 72 Grade X students from SMK Negeri 2 Depok, divided into an experimental class and a control class. The research instruments included expert validation sheets, practicality questionnaires administered to both teachers and students, and observation sheets assessing the implementation fidelity of the RME-based learning module. The findings indicate that the developed module achieved a